2013
DOI: 10.3390/ijms14046746
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of α-Lipoic Acid on Kidneys in Type 2 Diabetic Goto-Kakisaki Rats via Reducing Oxidative Stress

Abstract: To evaluate the protective effects of α-lipoic acid on the kidneys of Goto-Kakisaki (GK) diabetic rats, ten GK diabetic rats were randomly divided into a diabetic control group and a lipoic acid-treated diabetic group with α-lipoic acid 35 mg·Kg−1 intraperitoneal injections. Four healthy Wistar rats served as normal controls. Malonaldehyde (MDA), ascorbic acid (vitamin C), vitamin E, glutathione (GSH) and superoxide dismutase (SOD) levels in renal homogenate, and urine protein excretion were measured. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 22 publications
2
33
0
2
Order By: Relevance
“…In patients with diabetes, there is increased production of AGEs [28] and due to overgeneration of reactive oxygen species (ROS), causing an imbalance and produces OS [44]. GSH is a tripeptide present in all cells in micromolar concentrations has great antioxidative property [45,46]. Low levels of GSH in T2DM patients in our study are in accordance withfindings of other studies [47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 92%
“…In patients with diabetes, there is increased production of AGEs [28] and due to overgeneration of reactive oxygen species (ROS), causing an imbalance and produces OS [44]. GSH is a tripeptide present in all cells in micromolar concentrations has great antioxidative property [45,46]. Low levels of GSH in T2DM patients in our study are in accordance withfindings of other studies [47][48][49][50][51].…”
Section: Discussionsupporting
confidence: 92%
“…According to Feng et al [14] α-lipoic acid has effects on the kidneys of diabetic rats, increasing the levels of GSH, SOD, vitamins E, and C in ALA-treated group, compared to the diabetic group. Further evidence for in vivo efficiency of ALA in inflammatory diseases is given by the fact that ALA inhibits airway inflammation in a mouse model of asthma.…”
Section: Discussionmentioning
confidence: 99%
“…78 Several studies have reported that GK rats exhibit the common histological changes in the kidneys that are observed in other animal models of diabetes, including thickening of glomerular basement membranes, mild to moderate mesangial matrix expansion, glomerular hypertrophy, oxidative stress, and inflammation. [79][80][81] However, even older GK rats do not exhibit progressive renal damage, which is characterized by the development of global glomerulosclerosis, marked mesangial matrix expansion, nodular formation, progressive proteinuria, tubulointerstitial fibrosis, and renal dysfunction.…”
Section: Wf Ratsmentioning
confidence: 99%